Rola interesariuszy prywatnych i instytucjonalnych w kształtowaniu odpowiedzialności społecznej organizacji - Banasiewicz, Kazimierz (Corporate Social Responsibility and the Role of Private and Institutional Stakeholders, 2009)
The paper shows two relations between organizations and their private and institutional stakeholders. The aim of the paper is to conclude that the Corporate Social Responsibility gives some regulations to decrease negative results of economic theory of regulation.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 98-105